Design and evaluation of plagiarism prevention and detectiontechniques in engineering education. Issue 1 (1st January 2019) - Halak, Basel; El-Hajjar, Mohammed
ABSTRACT: Higher education students are expected to develop critical analysis and creative thinking skills, where plagiarism can damage the development of these skills in addition to damaging the whole education process and experience. Furthermore, plagiarism undermines the trust between the lecturers and students and the reputation of the academic institutions can be affected if plagiarism is not considered seriously, where the degrees offered by these institutions can be devalued. In this paper, two plagiarism prevention techniques followed by two plagiarism detection techniques used in the engineering education in the University of Southampton are presented. The plagiarism prevention techniques presented are based on assigning individual coursework specifications to students and the use of individual presentation of coursework findings. Then, the plagiarism detection techniques are based on detecting the writing styles of students and testing the student' codes in different configurations.